2018
DOI: 10.21071/az.v67i258.3651
|View full text |Cite
|
Sign up to set email alerts
|

Performances de croissance, de ponte et qualité de l’œuf chez la caille Japonaise (Coturnix coturnix japonica)

Abstract: Le présent travail a consisté à étudier les performances de croissance (durant 6 semaines) et de ponte (9ème-12ème semaine) de Coturnix coturnix japonica ainsi que la qualité interne et externe des œufs. Au total, 300 cailleteaux de 1 jour d’âge ont été menés au sol. Á 6 semaines d’âge, le poids vif (PV) moyen a été de 162g avec un indice de consommation de 3,59. Les mensurations effectuées à l’âge de 8 semaines ont montré un dimorphisme sexuel significatif (P

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Consequently, the shape index obtained for SF0 and SF5 is higher than that of SF10. These results are closest to those found by Ouaffai et al (2018) who found values of 3,25 and 2,54 cm for length and width, so 78,2 for shape index. Also, feed supplementation with sunflower oil increased the length and width of quail eggs (P<0.0001) in agreement with results found by Lohmann (2018) when laying hens received diets supplemented with soybean oil.…”
Section: Eggs Qualitysupporting
confidence: 86%
“…Consequently, the shape index obtained for SF0 and SF5 is higher than that of SF10. These results are closest to those found by Ouaffai et al (2018) who found values of 3,25 and 2,54 cm for length and width, so 78,2 for shape index. Also, feed supplementation with sunflower oil increased the length and width of quail eggs (P<0.0001) in agreement with results found by Lohmann (2018) when laying hens received diets supplemented with soybean oil.…”
Section: Eggs Qualitysupporting
confidence: 86%
“…The best ADG values (AC 2: 6.67 g/d and AP 2: 5.92 g/d) obtained in the present study at week 5 were much higher than those obtained by other authors. This is the case of [2], [18], [21] as well as [25] who respectively obtained 3.91 g/d; 3.41 g/d to 3.65 g/d; 3.69 g/d and 3.64 g/d. ADGs close to those of this study were also obtained by [33], [35] as well as [42].…”
Section: Discussionmentioning
confidence: 64%
“…At the same age, [23] obtained LWs ranging from 168.2 to 173.8 g in three different varieties of Coturnix japonica. Besides all these differences, other authors such as [24] and [25] obtained LW of 157.3 g and 162.4 g respectively. In younger quails (4-5 weeks old), [26] recorded higher LWs (242.1 and 284.9 g, respectively) than those obtained at the same age in the present study.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations